2019
DOI: 10.1071/rd18277
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide reduces gonadotrophin-releasing hormone (GnRH) gene expression: role of RFamide-related peptide-3 and kisspeptin

Abstract: RFamide-related peptide (RFRP)-3 reduces luteinising hormone (LH) secretion in rodents. Stress has been shown to upregulate the expression of the RFRP gene (Rfrp) with a concomitant reduction in LH secretion, but an effect on expression of the gonadotrophin-releasing hormone (GnRH) gene (Gnrh1) has not been shown. We hypothesised that lipopolysaccharide (LPS)-induced stress affects expression of Rfrp, the gene for kisspeptin (Kiss1) and/or Gnrh1, leading to suppression of LH levels in rats. Intracerebroventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
1
16
1
Order By: Relevance
“…changing RFRP3 levels (Iwasa et al, 2015;Lee et al, 2019). Moreover, it has been reported that an icv administration of RFRP3 does not affect Gnrh or Kiss1 expression (Lee et al, 2019). In our study, we found that a high dose of LPS increased Rfrp3 levels and decreased Gnrh and Kiss1 levels, although we cannot discern if RFRP3 directly participates in the inhibition of the stimulatory neuropeptides.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…changing RFRP3 levels (Iwasa et al, 2015;Lee et al, 2019). Moreover, it has been reported that an icv administration of RFRP3 does not affect Gnrh or Kiss1 expression (Lee et al, 2019). In our study, we found that a high dose of LPS increased Rfrp3 levels and decreased Gnrh and Kiss1 levels, although we cannot discern if RFRP3 directly participates in the inhibition of the stimulatory neuropeptides.…”
Section: Discussioncontrasting
confidence: 49%
“…changing RFRP3 levels (Iwasa et al, 2015;Lee et al, 2019). Moreover, it has been reported that an icv administration of RFRP3 does not affect Gnrh or Kiss1 expression (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data presented that the kisspeptin system is sensitive to inflammation. Systemic endotoxin injection (LPS) in female rat decreases KISS-1 mRNA expression in the hypothalamus that consequently suppresses LH [91,92]. Moreover, intravenous (i.v.)…”
Section: Kisspeptin and Rfamide-related Peptides Mediate Inflammationmentioning
confidence: 99%
“…Inflammation may inhibit GnRH secretion via alteration of the RFRP system as LPS injection has been demonstrated to elevate hypothalamic RFRP and GPR147 mRNA levels in rodents [91,92]. Since RFRPs modulate kisspeptin signaling, inflammation might also have an effect on GnRH pulse generation via the RFRP system.…”
Section: Kisspeptin and Rfamide-related Peptides Mediate Inflammationmentioning
confidence: 99%